Análise da qualidade da informação do site “Quanto Custa Viajar” em relação ao modo tradicional de pesquisa de modais envolvendo a atividade turística - Macedo, Alexya Cristina Alabi (Universidade Estadual Paulista (Unesp), 2021)
This research sought an answer to the following question: can the website "Quanto Custa Viajar" present itself as a new and important travel business model against the traditional mode of supply? For this question, it was proposed, as the main objective of the research, the analysis of the site "Quanto Custa Viajar" offer formatting against the traditional way of searching for modes involving the tourist activity, having as specific objectives the identification of the operational structure of the offer based on the Shared Economy precepts in order to point out the effectiveness of the site offer compared to the traditional offer sites focused on Tourism. To achieve the objectives, the study was developed in parts: the work was presented to the participants through online tools, the research was directed to a navigation on the site "Quanto Custa Viajar" and in others that generate the experience of package configuration and then they were submitted to a questionnaire by Google Forms with a maximum total of 1 open question and 10 closed questions about their perceptions. Thus, the stipulated number of participants was a minimum of 100 people, constituting a convenience sample. Thus, the study is qualitative in nature. According to the results of this evaluation, it was possible to observe that the indicated site is interesting, but needs improvements in terms of information, organization and functionality to be able to offer what traditional sites offer, that is, to have the option of reservations, ticket sales/entries, without having to resort to the supplier's official sites, making the site limited.

Esta pesquisa buscou resposta para a seguinte questão: o site “Quanto Custa Viajar” pode apresentar-se como um novo e importante modelo de negócio de viagens frente ao modo tradicional de oferta? Para essa questão, foi proposto, como objetivo principal da pesquisa análise da formatação da oferta do site “Quanto Custa Viajar” contraposta ao modo tradicional de pesquisa de modais envolvendo a atividade turística, tendo como objetivos específicos a identificação da estrutura de funcionamento da oferta pautada nos preceitos da Economia Compartilhada com vistas ao apontamento da efetividade da oferta do site comparada aos sites de ofertas tradicionais voltados ao Turismo. Para alcançar os objetivos, o estudo foi desenvolvido em partes: o trabalho foi apresentado para os participantes a partir de ferramentas “online”, a pesquisa dirigiu-se para uma navegação no site “Quanto Custa Viajar” e em outros que gerem a experiência de configuração de pacotes e na sequência foram submetidos a um questionário pelo Google Forms com um total máximo de 1 questão aberta e 10 fechadas a respeito de suas percepções. Assim, o número estipulado de participantes mínimo de 100 pessoas, constituindo uma amostra por conveniência. Desse modo, o estudo é composto por natureza qualitativa. Segundo os resultados desta avaliação, foi possível observar que o site indicado é interessante, porém necessita de melhorias em questão de informação, organização e funcionalidade para conseguir oferecer o que os sites tradicionais oferecem, isto é, possuir a opção de reservas, vendas de passagens/entradas, sem precisar recorrer aos sites oficiais do fornecedor, tornando o site limitado.
Analysis of the quality of information on the site “Quanto Custa Viajar” in relation to the traditional way of researching modals involving tourism activity
Keywords: Tourism; Sharing economy; Turismo; Viagens; Economia compartilhada; Tecnologia; Sites da Web